2013
DOI: 10.1021/am403085y
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Magnetic Field-Assisted Low Temperature Atmospheric Growth of GaN Nanowires via the Vapor–Liquid–Solid Mechanism

Abstract: We report the growth of GaN nanowires at a low temperature of 750 °C and at atmospheric pressure in a conventional chemical vapor deposition (CVD) setup via the vapor-liquid-solid mechanism with remarkable control of directionality and growth behavior by using an in situ magnetic field. Under typical growth conditions, without any magnetic field, the nanowires are severely twisted and kinked, and exhibit a high density of planar stacking defects. With increasing in situ magnetic field strength, the microstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Initially, a Ni thin‐film layer with different film thickness is deposited by direct current (DC) sputtering. An AlNiCo magnet was then placed on top of the Ni‐deposited substrate to produce a uniform array of nanodots by annealing the Ni thin layer at 750 °C under the influence of magnet . During the annealing, a Ga gaseous source is provided to facilitate the consolidation process into liquid droplets at the temperature of 750 °C.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Initially, a Ni thin‐film layer with different film thickness is deposited by direct current (DC) sputtering. An AlNiCo magnet was then placed on top of the Ni‐deposited substrate to produce a uniform array of nanodots by annealing the Ni thin layer at 750 °C under the influence of magnet . During the annealing, a Ga gaseous source is provided to facilitate the consolidation process into liquid droplets at the temperature of 750 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The final film/electrode structure corresponds to Pt/Nb‐doped PZT/Ir/TiW/Ni nanodots/SiO 2 /Si. The role of magnet used here provides uniform external magnetic field strength to facilitate consolidation of the Ni nanodots at high temperature, as reported by our group . The existence of Ni nanodots incurs extra compressive stress in the initial stage of film growth due to an enormous difference of ≈94% in thermal expansion coefficient (TEC) between the PZT film and Ni.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…The SSD technique has typically been used to fabricate nanodot arrays with diameter from tens to hundreds nanometers, which are important elements in a variety of nanodots-based applications, including high-density magnetic recording media12, solar cells34, catalysts for nanowire growth56, and many plasmonic devices, such as plasmon-resonance wave guides78, plasmon-enhanced photovoltaic devices910, plasmonic LEDs1112, and biosensors13. Our recent work14 showed that SSD can also be used to fabricate nano-aperture arrays with high yield and at low costs.…”
mentioning
confidence: 99%